Promising Approaches to Address the needs of Poor Women Farmers: A solution to the food price crisis? - Quisumbing, Agnes R.; Pandolfelli, Lauren (2009)
Agnes R. Quisumbing and Lauren Pandolfelli 17th June 2008, International Food Policy Research Institute, Washington D.C.